Downregulation of the vitamin D receptor expression during acute gastrointestinal graft versus host disease is associated with poor outcome after allogeneic stem cell transplantation - Matos, Carina; Mamilos, Andreas; Shah, Pranali N.; Meedt, Elisabeth; Weber, Daniela; Ghimire, Saroj; Hiergeist, Andreas; Gessner, André; Dickinson, Anne; Dressel, Ralf; Walter, Lutz; Stark, Klaus; et al. (Frontiers in Immunology, 2022)
The vitamin D receptor (VDR) is critical in regulating intestinal homeostasis and emerging evidence demonstrates that VDR deficiency is a critical factor in inflammatory bowel disease pathology. However, no clinical data exist regarding the intestinal expression of VDR in patients after allogeneic haematopoietic stem cell transplantation (HSCT). Analyzing intestinal biopsies from 90 patients undergoing HSCT with mortality follow-up, we demonstrated that patients with severe acute gastrointestinal graft versus host disease (GI-GvHD) showed significant downregulation of VDR gene expression compared to mild or no acute GI-GvHD patients (p = 0.007). Reduced VDR expression was already detectable at acute GI-GvHD onset compared to GvHD-free patients (p = 0.01). These results were confirmed by immunohistochemistry (IHC) where patients with severe acute GI-GvHD showed fewer VDR+ cells (p = 0.03) and a reduced VDR staining score (p = 0.02) as compared to mild or no acute GI-GvHD patients. Accordingly, low VDR gene expression was associated with a higher cumulative incidence of treatment-related mortality (TRM) (p = 1.6x10-6) but not with relapse-related mortality (RRM). A multivariate Cox regression analysis identified low VDR as an independent risk factor for TRM (p = 0.001, hazard ratio 4.14, 95% CI 1.78-9.63). Furthermore, VDR gene expression significantly correlated with anti-microbial peptides (AMPs) gene expression (DEFA5: r = 0.637, p = 7x10-5, DEFA6: r 0 0.546, p = 0.001). In conclusion, our findings suggest an essential role of the VDR in the pathogenesis of gut GvHD and the prognosis of patients undergoing HSCT.